Applying Usability and HCI Principles in Developing Marketing Websites - Issa, Tomayess; Turk, A. (M I R Publishers, 2012)
This paper discusses why application of usability and human computer interaction (HCI) principles is essential in development of effective websites for marketing purposes. The poor usability of many websites wastes users' time, and increass their frustration. The paper explains how usability and HCI aspects were included in the new Participative Methodology for Marketing Websites, to reduce user frustration and to improve the website capabilities. This new methodology was developed after intensive study and methodologies from Information Systems Development, Methodologies for Developing Websties, Marketing Methodologies and additional detailed design techniques. The participative Methodology for Marketing Websites was assessed by two research phases: interview and questionnaire. This paper includes only two aspects of the full research process: an overview of the research methodology; and discussion the results from the interview and questionnaire study, focusing on usability and HCI aspects.